Mindfulness and Symptoms of Depression and Anxiety in the General Population: The Mediating Roles of Worry, Rumination, Reappraisal and Suppression - Parmentier, Fabrice B. R.; García-Toro, Mauro; García-Campayo, Javier; Yañez, Aina M.; Andrés, Pilar; Gili, Margalida (Frontiers in Psychology, 2019)
The present study examined the effects of mindfulness on depression and anxiety, both direct and indirect through the mediation of four mechanisms of emotional regulation: worry, rumination, reappraisal and suppression. Path analysis was applied to data collected from an international and non-clinical sample of 1151 adults, including both meditators and non-meditators, who completed an online questionnaire battery. Our results show that mindfulness are related to lower levels of depression and anxiety both directly and indirectly. Suppression, reappraisal, worry and rumination all acted as significant mediators of the relationship between mindfulness and depression. A similar picture emerged for the relationship between mindfulness and anxiety, with the difference that suppression was not a mediator. Our data also revealed that the estimated number of hours of mindfulness meditation practice did not affect depression or anxiety directly but did reduce these indirectly by increasing mindfulness. Worry and rumination proved to be the most potent mediating variables. Altogether, our results confirm that emotional regulation plays a significant mediating role between mindfulness and symptoms of depression and anxiety in the general population and suggest that meditation focusing on reducing worry and rumination may be especially useful in reducing the risk of developing clinical depression.